Ticari işlemlerde taşınır rehninin sona ermesi - Kara, Burak (My University, 2018)
ÖZETBir alacağın ifasını teminat altına almak adına alacağa bağlı olarak ayni ve şahsi teminat sağlayan hukuki kurumlar bulunmaktadır. Hukukumuzda alacağa ayni teminat sağlama görevini üstlenen teminat aracı rehin hakkıdır. 01.01.2017 tarihi itibarıyla yürürlüğe giren Ticari İşlemlerde Taşınır Rehni Kanunu (TRK) da teslime bağlı olmayan taşınır rehnini düzenleyen özel bir kanundur. Çalışmamızda genel rehin hukuku ilkelerini de dikkate alarak bu özel kanuna göre kurulan taşınır rehin hakkının sona ermesinin izahına çalışmış bulunuyoruz. Çalışmamızın ilk bölümü; TRK’nın amacı, uygulama alanının tespiti, çeşitli taşınır rehin haklarının sona ermesine ilişkin kendi kanunlarında yer alan düzenlemelerin incelenmesi ve TRK’ya göre kurulan rehin hakkının sona ermesiyle ilgili hükümlerin genel bir değerlendirilmesine ayrılmıştır. Rehin hakkının anılan kanuna göre kurulması Rehinli Taşınır Sicili’ne tescil ile gerçekleştiğinden sona ermesinde de hakkın maddi anlamda sona ermesiyle şekli anlamda sona ermesi (sicilden terkini) ayrımlarının yapılması gerekmektedir. Bu ayrıma uygun olarak çalışmamızın ikinci bölümünde maddi anlamda rehin hakkının sona ermesi; üçüncü bölümünde ise rehin hakkının şekli anlamda sona ermesi incelenmiştir.

ABSTRACTThere are personel and real security components that guarantee the performance of obligation. In our legal system, guarantee instrument undertaking the task of providing the real security for the right to claim is pledge. As of 01.01.2017, the Law on Movable Pledge in Commercial Transactions (TRK), which is in force in our law, is a special law regulating movable pledge which is not tied to delivery of possession. We have also worked on the explanation of the termination of the movable pledge established in accordance with this special law, taking into account the general pledge law principles in our work. The first part of our work was devoted to the determination of the purpose of the TRK, the determination of the application area of the TRK, the examination of the regulations contained in its law concerning the end of various movable pledge rights and a general evaluation of the provisions related to the ending of the pledge right established in accordance with TRK.Since the establishment of the pledge is carried out with the registration of the Pledged Portable Registry, it is necessary to make a distinction between the end of the right in material meaning and the end of the right in meaning of form (erasure of entry in register). In the second part of our work in accordance with this separation, the right of pledge in the material sense ends; in the third part, the end of the pledge right in the formal sense has been examined.
Keywords: Ayni Teminat; Commercial Enterprise; Commercial law; Erasure; Extinction ofSecurity; Movable Pledge; Pledges (law); Rehin (Hukuk); Rehnin Sona Ermesi; Taşınır Rehni; Terkin Real Security; Ticaret hukuku; Ticari İşletme; Turkey; Türkiye